Lifestyles in residents from Santiago de Cuba municipality - Raxsy Soler Santana; Imilsy Delgado Matos; Mayelin Marin Méndez (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Noncommunicable diseases represent one of the greatest challenges in the development of nations in the 21st century. Objective: To characterize a population from Santiago de Cuba municipality according to lifestyles. Methods: An observational, descriptive and cross-sectional study was carried out during the year 2020, of 1265 residents in Santiago de Cuba municipality selected from a randomized, proportional and stratified sample design, whom a survey that included sociodemographic and lifestyle aspects was applied. The information obtained was processed by using summary measures for qualitative and quantitative variables. Results: In the series, it was determined that 24.3% of Santiago population used tobacco, predominantly in men (57.7%), and that 38.8% were exposed to other people's tobacco smoke at home. Likewise, alcohol use appeared in 46.8%, walking to get around was the physical activity mostly carried out in 43.2%, and overweight and obesity prevailed in 59.3%. Conclusions: In Santiago de Cuba municipality, tobacco consumption, inadequate dietary habits, low physical activity, overweight and obesity were identified as unhealthy lifestyles that increase the risk of suffering from noncommunicable diseases.